Six-Minute Walk as a Measure of Walking Capacity and Endurance in Patients With Pediatric-Onset Multiple Sclerosis. (8th November 2022) - Brenton, J. Nicholas; Florenzo, Brian; Koshiya, Hitoshi; Min, Seulgi; Woolbright, Emma; Coleman, Rachael; Chen, Shanshan; Goldman, Myla
Abstract : Background and Objectives: Despite low levels of disability, youth with pediatric-onset multiple sclerosis (POMS) engage in less physical activity compared with peers. The contribution of walking capacity, endurance, behavior, and MS comorbidities remains relatively undefined and may provide valuable insights into the limitations toward physical activity in youth with MS. The primary objective of this study was to investigate differences in walking capacity, endurance, and real-world behaviors of daily activity between youth with POMS and controls. Methods: Youth diagnosed with MS prior to 18 years and aged 21 years or younger were recruited in addition to healthy controls. Participants completed questionnaires to quantify fatigue, depression, and physical activity levels and the timed 2- and 6-minute walk (6MW) as an assessment of walking capacity and endurance. Participants completed questionnaires to quantify fatigue, depression, and physical activity levels. Participants also completed the timed 2- and 6-minute walk (6MW) as an assessment of walking capacity and endurance and were sent home with a waist-worn accelerometer to assess real-world walking behavior. Results: Forty-five patients with POMS and 85 control participants were enrolled. The POMS cohort had a mean age of 16.9 ± 2.7 years, with a mean disease duration of 2.8 ± 2.6 years. A greater proportion of the POMS cohort was overweight/obese compared with controls (75% vs 33%). Participants with MS walked a significantly shorter distance in 6 minutes compared with controls (1, 848 feet vs 2, 134 feet, p < 0.0001) and, unlike controls, were unable to accelerate to their peak speed at the end of the 6MW. Body mass index category and MS disease significantly affected 6MW performance. Using continuous accelerometry, participants with MS spent less time in moderate-to-vigorous physical activity compared with controls (20.4 vs 35.4 min/d, p = 0.0003). The POMS cohort reported significantly higher levels of depression and fatigue but self-reported similar levels of daily physical activity as controls. Discussion: Youth with POMS exhibit slower 6MW performance and less daily engagement in moderate-to-vigorous physical activity, suggesting limitations in functional walking capacity, endurance, and daily activity behavior. Limitations in walking endurance and capacity are most prominent in those youth who are overweight/obese and living with MS. Classification of Evidence: This study provides Class III evidence that, compared with healthy controls, patients with POMS walk shorter distances on the 6MW test, are less able to accelerate to peak speed at the end of the test, and are less physically active.